2021
DOI: 10.3329/bjms.v20i5.55419
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation of Social Media Activity and Engagement of a Health NGO with the Outcome of Fundraising Efforts During the COVID-19 Pandemic

Abstract: Objective: The COVID-19 pandemic saw the involvement of many health non-governmental organisations (NGO) with volunteering work to help reduce the burden of healthcare workers (HCW). IMAM Response and Relief Team (IMARET) is one which is a chapter under the Islamic Medical Association of Malaysia (IMAM); which is also under the umbrella of the Federations of Islamic Medical Associations (FIMA). IMARET often aids HCWs during natural and manmade disasters to help reduce their burden during challenging times by p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Zinc supplementation can be a helpful system to lessen the worldwide weight of disease in the older, there is a need the expanded answering to work on our comprehension of COVID-19 and the consideration of impacted patients 5 . Healthful mediations, including the supplementation of nutrients and minerals, in this manner agree to likely therapeutics for novel COVID-19, acting additionally about of the side effects of disease like loose bowels [2]. In any case, wholesome treatment shows up as first-line treatment and ought to be carried out into standard practice.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Zinc supplementation can be a helpful system to lessen the worldwide weight of disease in the older, there is a need the expanded answering to work on our comprehension of COVID-19 and the consideration of impacted patients 5 . Healthful mediations, including the supplementation of nutrients and minerals, in this manner agree to likely therapeutics for novel COVID-19, acting additionally about of the side effects of disease like loose bowels [2]. In any case, wholesome treatment shows up as first-line treatment and ought to be carried out into standard practice.…”
Section: Introductionmentioning
confidence: 80%
“…During the most recent twenty years, Covids have caused three plague of dangerous sickness: serious intense respiratory disorder (SARS), Middle East respiratory condition (MERS) and COVID-19. SARS-CoV-2 is by all accounts less destructive than SARS-CoV or MERS-CoV with death pace of 3.4%, 9.6% and ~35%, individually however seems, by all accounts, to be irresistible 2 . Coronavirus spread by human-to-human transmission through drop, and direct contact and has a hatching time of 2-14 days 3 .…”
Section: Introductionmentioning
confidence: 93%
“…It can be partially true because a majority of advancements in dental education have been confined to dental schools in developed nations, leading to a growing disparity between established institutions and those in economically disadvantaged countries. This may impact their chances of finding employment or acceptance in certain countries 12,13 .…”
Section: Discussionmentioning
confidence: 99%
“…However, social media has been positive with alleviating concerns with personnel and funding to address the challenges faced particularly by lowincome countries with addressing the pandemic. Encouragingly in their paper, Rashid et al found that the likes, reach, and shares of Facebook and other posts, significantly correlated with the number and extent of donations during the initial phases of the IMAM Response and Relief Teams (IMARET) under the Islamic Medical Association of Malaysia 51 . This has important implications for the future.…”
Section: The Instigation Of Large Multi-arm Studies Including the World Health Organisation (Who) Solidaritymentioning
confidence: 97%